MANAGING RELIGIOUS AND ETHNIC DIVERSITY FOR PEACE AND HARMONY: ISLAM AND BUDDHISM IN THE MALAY WORLD OF SOUTH EAST ASIA - Imtiyaz Yusuf (Universitas Islam Negeri Raden Fatah Palembang, 2017)
This article discusses the phenomenon of the relationship between Islam and Buddhism in the Malay World of Southeast Asia. The ultimate goal is to uncover social facts about the relationship between adherents of the two largest religions in Southeast Asia: Islam (42%) and Buddhism (40%). This research shows that the relations between Islamic and Buddhist communities in various Southeast Asian Countries are full of dynamics. The dynamics can take the form of peaceful relations or vice versa: conflicts with various levels of escalation. Among the reasons that also triggered the emergence of conflict is the problem of political, economic, socio-cultural, and religious disparities. The solution to this problem can be done with a historical approach, an intra and interfaith dialogue approach in order to foster mutual understanding between adherents of both religions, a political policy approach in the form of granting basic rights to followers of a minority religion, and an academic approach through the study of religions in various universities in Thailand, Malaysia, Singapore, Indonesia and various other countries in the Southeast Asian region. Meanwhile, Islamic studies in various Islamic universities need to be done with an interdisciplinary approach and understanding of languages ​​and cultures that exist in Asian countries.